EL FALLO PRAGMÁTICO EN LA TRADUCCIÓN AL ESPAÑOL DE TIME AND THE CONWAYS Y LOOK BACK IN ANGER - Fernández Amaya, Lucía (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract Some bilingual people, although able to use two or more languages and speak correctly grammatically, sometimes use the language inappropriately. Thus, for instance, when a speaker mentions something taboo, the hearer, who has not heard anything ungrammatical, does not interpret the utterance as a mistake but rather as impolite. As can be seen, these mistakes, called by Thomas (1983) pragmatic failures, are very important because they can cause a breakdown in communication. Thomas defines pragmalinguistic failure as “...the inability to understand ‘what is meant by what is said’” (1983: 91). This author argues that a speaker’s linguistic competence is made up of grammatical competence – abstract or decontextualized knowledge of syntax, semantics, etc. – and pragmatic competence – the capacity to use language effectively to achieve a given goal and to understand language in context. Therefore, a bilingual person’s linguistic knowledge must consist of both types of competence. However, this is not always the case, and when pragmatic competence is not present, the result is pragmatic failure. In order to show the kind of pragmatic errors that a bilingual person can make, I will analyze some examples taken from the English plays Look Back in Anger and Time and the Conways and their translations into Spanish.